Aktywność enzymatyczna gleb na obszarach sztucznej i naturalnej regeneracji lasu po klęsce huraganu w północno-wschodniej Polsce - Olszowska, Grażyna (Leśne Prace Badawcze, 2016)
The aim of the study was to describe biochemical reactions in the soil based on the activity of urease and dehydrogenases in Scots pine stands damaged during and differentially managed after hurricanes. Soil enzymatic activity was investigated in 2005 and again in 2013 for selected stands in the Pisz Forest District where wind damage occurred in 2002. Most of the damaged stands were cut down and replanted, but 445 ha were left untouched for study purposes. The investigated areas differed with respect to stand damage and management. The enzymatic activity correlated well with the content of organic matter which was higher in organic than in mineral soils. In the area left to regenerate naturally, dehydrogenase and urease activity was higher in 2013 compared to 2005, which suggests the improvement of site conditions. The values of the examined biochemical parameters were correlated with the type of forest regeneration, with the forest soil regeneration being higher in artificially than in naturally regenerated stands. Changes of soil enzymatic activity were correlated with the level of stand damage and the type of management after wind damage.